Leadership in the Research: Determinants of Quality, Standards and Best Practices - Henryk Dźwigoł (Business Ethics and Leadership)
One of the obligatory elements of any scientific research is a methodical toolkit, the diversity of which determines the reliability of the obtained results and ability to solve the tasks set in the work. The purpose of the article is to identify the factors defining the scientific research process and affect the quality of the results. The methodological tools of the study include questionnaires and factor analysis (Bartlett’s test for sphericity, KMO test (Kaiser-Meyer-Olkin sampling adequacy measure), and MSA test (sampling adequacy measure)). The object of research is 401 scientists and 196 practitioners in the field of management and quality sciences. The questionnaire for practitioners consisted of four parts. The first part includes general issues about the research process, methods and techniques used in it; the second deals with the importance of using methods and techniques in the scientific research in the field of management and quality sciences; the third – provides questions on improving the quality of research; the fourth is demographic. The questionnaire for scientists consists of three parts. The first part addresses the importance of approaches, processes, methods and techniques in research in the field of management and quality sciences; the second – includes questions on improving the research process; the third is demographic. The results are summarized on a five-point Likert scale. Based on the generalization of practitioners’ answers, the main factor of scientific research is the “concept of the research methodology model”, defined as a measure of the scientific research process effectiveness. The results of the analysis help conclude the need to develop new research methods that can increase its effectiveness by managing, planning, organizing and verifying the research process in the field of management and quality sciences. The factors determining the research process and affecting its quality include constant changes in the market. It necessitates the use of various research methods that can form a holistic basis for empirical analysis. The research process quality means checking the degree of implementation and consistency of the objectives in the article with the research problem and the conclusions in it. For the effective functioning of the research process, it is proposed to develop an “algorithm of behavior” of the researcher, which will (after determining the appropriate gap between research methods and features of the research problem) ensure their coordination and increase the added value of the results.